The Role of Center for Broadcasting Development Studies in Improving Professional Education in Indonesia - Idris, Naswil (FIkom Unisba, 2001)
A change of power in Indonesia marked a change of paradigm concerning almost every aspect of social political life in the country. Among those changes are the reinterpretation of the government role concerning the information control and freedom of press. As consequences of the strengthening of people power and their awareness to apply social control, press paradigm – including broadcasting- also changed. After 1998 reform, people became aware that broadcasting should be used for the people, by the people, and for the benefit of the people. In accordance with this situation, which is provoked by the elimination of the Ministry of Information, there is a need to establish the Center for Broadcasting Development Studies.